BISPHOSPHONATE THERAPY IN PEDIATRIC PATIENTS WITH OSTEOGENESIS IMPERFECTA - Alina Murgu; Roxana Cretu; Adnana Jaramani; Elena Macsim; Ana Maria Chiforeanu (Amaltea Medical Publishing House, 2015)
Osteogenesis imperfecta (OI) is a group of rare inherited disorders of connective tissue with the common feature of excessive fragility of bones caused by mutations in collagen. We present the case of 2 patients diagnosed with different types of OI, both males, one admitted in the neonatal period and one in infancy. The aim of the study was to compare the effi ciency of bisphosphonate therapy, following up the quality of life after receiving it, or in the absence of this treatment.